Nigeria’s Evolving Presence in Cyberspace - Mbanaso, Uche; Chukwudebe, Gloria; Atimati, Ehinomen (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2015)
Cyberspace is now critical to every nation’s socio-economic, cultural and political activities. When it is disrupted or fails, a country may experience strong adverse effects. On the contrary, its correct functioning and pliability is transforming modern society with exceptional pecuniary and social benefits. With many activities increasingly moving to the Internet, cyberspace has become a new stage for innovations, enterprises, social networking, criminality and war. This paper presents a brief overview of a study on Nigeria’s presence in cyberspace. The Internet penetration growth and evolving Internet infrastructure provisioning in Nigeria were examined and a critical assessment of Nigerian presence in cyberspace was carried out between the months of August and September 2015, using the United Nations online presence index methodology. Web content, interactivity, the currency of information, downloadable documents and other data sets were used to compare various sectors of the Nigerian economy, including all tiers of government, academia and the organised private sector. The study revealed that the organised private sector and private educational institutions are doing better than government educational institutions and ministries.Actions for increasing presence in cyberspace and achieving e-governance for improved services and productivity in Nigeria and similar developing countries are recommended.
Keywords: cyberspace, information economy, e-governance, cyber innovations, online presence, Internet presence